Endoscopic Diagnosis of Pyriform Fossa Lymphoma - A Thomson; P Marlton (Canadian Journal of Gastroenterology)
Many endoscopists do not inspect the gastrointestinal tract superior to the cricopharyngeus, despite the fact that gastrointestinal symptoms (dysphagia, odynophagia and chest pain) can be produced by glottic and supraglottic lesions. A case of incoordinate swallowing secondary to a right-sided pyriform fossa lymphoma diagnosed at gastroscopy is presented.